2012
DOI: 10.1159/000343189
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Auditory Performance of Postlinguistically Deaf Adults Using Cochlear Implants: An Update with 2251 Patients

Abstract: Objective: To update a 15-year-old study of 800 postlinguistically deaf adult patients showing how duration of severe to profound hearing loss, age at cochlear implantation (CI), age at onset of severe to profound hearing loss, etiology and CI experience affected CI outcome. Study Design: Retrospective multicenter study. Methods: Data from 2251 adult patients implanted since 2003 in 15 international centers were collected and speech scores in quiet were converted to percentile ranks to remove differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
528
10
32

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 546 publications
(615 citation statements)
references
References 99 publications
45
528
10
32
Order By: Relevance
“…The large range of CI outcomes that we observed, as well as the mean performance, is consistent with previous reports from large-scale, international studies (13)(14)(15), indicating that the CI outcomes observed in the present study may be considered representative of the wider CI population.…”
Section: Resultssupporting
confidence: 92%
“…The large range of CI outcomes that we observed, as well as the mean performance, is consistent with previous reports from large-scale, international studies (13)(14)(15), indicating that the CI outcomes observed in the present study may be considered representative of the wider CI population.…”
Section: Resultssupporting
confidence: 92%
“…Blamey [3] ermittelte den Einfluss der CI-Nutzungsdauer als wichtigsten Einflussfaktor für die mit dem CI erreichten Hörleistungen. Im ersten Jahr nach der Implantation wurde der größte Leistungszuwachs beobachtet.…”
Section: Ci-nutzungsdauerunclassified
“…In post-linguistically deaf adults, duration of auditory deprivation is a factor known to contribute to speech recognition ability after implantation [Blamey et al, 1996]. Additional factors contribute to outcome variability, e.g., pre-implant residual hearing [Rubinstein et al, 1999], but to date none of the identified clinical variables fully explains all of the variability [Blamey et al, 1996;Giraud and Lee, 2007;Green et al, 2007]. Other factors may intervene, including the amount and trajectory of cerebral plasticity that may have taken place during the period of deafness [Giraud and Lee, 2007;Lazard et al, 2010b;Strelnikov et al, 2010].…”
Section: Introductionmentioning
confidence: 99%